Analysis of Factors Affecting Egg Consumer Prices in Türkiye Using Random Forest Regression - Polat, M (FapUNIFESP (SciELO), 2025)
ABSTRACT Despite the substantial increase in egg production and consumption in Türkiye in recent years, price fluctuations remain prevalent. Forecasting consumer prices for eggs is, therefore, a complex endeavor. This study analyzed various factors affecting egg prices, including layer hen feed price, corn and sunflower meal costs, wheat prices, distillers dried grains with solubles (DDGS) prices, the dollar exchange rate, the producer price index (PPI), and agricultural PPI data spanning January 2010 - April 2022. The dataset comprised 148 monthly data points influencing unitary egg prices. Random forest regression analysis was employed to investigate the determinants of consumer egg prices in Türkiye. Results indicated that economic indicators such as the exchange rate, feed price, and producer price index significantly impact egg prices. The random forest regression model exhibited high explanatory power (R2=% 95.2) in predicting egg prices. This study enhances understanding of factors influencing consumer price fluctuations in the egg poultry sector, enabling stakeholders to make more informed and strategic decisions concerning egg prices.